2019
DOI: 10.9734/ajaees/2019/v35i230216
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Factors Affecting Poultry (Broiler) Production in Imo State, Nigeria

Abstract: The study assessed the factors affecting poultry (broiler) production in Imo State, Nigeria. Multistage sampling technique was used in selecting the respondents. A total of eighty four (84) poultry producers were randomly selected with the aid of well-structured questionnaire. Data were analyzed using descriptive statistics and multiple regression models. The result shows that majority (59.5%) of the producers were male, mean age was 45 years, mean household size was 6 persons, 67.86% of the producers attended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…This indicates that an improvement in the quantity of prescribed medications and vaccines would lead to 2.56% increase in production. The result is consistent with Etuah et al (2020) and Osuji (2019) who in their respective studies on poultry efficiency studies there found a positive and significant relationship between medication and output. The coefficient of labour had positive and significant relationship with output at 5%.…”
Section: Regression Results On Production Efficiency Of Exotic Chickensupporting
confidence: 91%
“…This indicates that an improvement in the quantity of prescribed medications and vaccines would lead to 2.56% increase in production. The result is consistent with Etuah et al (2020) and Osuji (2019) who in their respective studies on poultry efficiency studies there found a positive and significant relationship between medication and output. The coefficient of labour had positive and significant relationship with output at 5%.…”
Section: Regression Results On Production Efficiency Of Exotic Chickensupporting
confidence: 91%
“…To prevent a total collapse of the industry by protecting local farmers, the federal government of Nigeria introduced broiler anchor borrowers’ schemes (Central Bank of Nigeria, 2016). This has not yielded any desired results as the industry is still plagued by various constraints such as high cost of feed, disease outbreak, inadequate finance, poor infrastructure, competition with illegal importation among others (Adeyonu et al, 2021; Olorunwa, 2018; Osuji, 2019). The impact of these on the industry is enormous as it resulted in the closing down of the farms, reduction in the flock size, and prevention of new entrants into the industry.…”
Section: Introductionmentioning
confidence: 99%
“…16, 1057.65, 52.2, and 12.39 million rural, meat type, egg type, and breeding stock of poultry birds, respectively [2]. In developed countries, poultry breeders play an important role in the conservation of the genetic diversity of poultry species (meat-type birds), but also contribute in the production of adequate quantities of high-quality animal protein that are necessary for covering the consumption needs of the rapidly increasing human population [3]. In Pakistan, meat from poultry is about 32.7% of the total meat available in the country for human consumption [4].…”
Section: Introductionmentioning
confidence: 99%